Physical Education as a Solution to Obesity in Children - Muhammad Akbar Syafruddin; Nur Indah Atifah Anwar; Agus Sutriawan; Suparman Suparman (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This research is a qualitative descriptive study that aims to find out the role of physical education as a solution to solving the problem of obesity in children in this modern era. The method applied in this study is a literature study that was excavated from various studies sourced from Google Scholar using the keywords physical education and obesity. The conclusion of this study is that physical education can help obese students achieve their lifelong health and fitness goals through fitness improvement approaches and counselling related to healthy lifestyles and the dangers of obesity.